Design and engineer a domestic use vertical farm unit for growing green vegetables and herbs (project 3) - Yap, Jonathan Hao Yi (2017)
As the population of Singapore and its demand for food continues to increase, there is a need for more sustainable sources of food. With the potential of utilizing vertical farming units to grow vegetables and herbs in individual households, the objective of this report was to determine a sustainable, cost-effective and energy efficient design of a vertical farming system which can be operated for indoor use in places such as Housing & Development Board (HDB) flats or similar apartments as well as to explore the concept of utilizing fibre optics as a substitute to grow lights. A series of prototypes were built and tested before arriving to the design of the final product. The structure of the final product was modular allowing for the ease of assembly and customization. It made use of hydroponics, with a combination of a nutrient film technique and a wick system, to grow green vegetables and herbs, and was also effective at germinating seeds, growing young seedlings to full maturity as well as ‘regrowing’ previously harvested herbs and vegetables. It also portrayed the capabilities of utilizing fibre optic cables, paired with a solar tracker and collector dish for the transference of natural sunlight indoors to illuminate the vertical farming system. Different from other indoor vertical farming systems, this system prides itself on achieving a low carbon footprint, comparable to the energy output of just one 50W light bulb. By utilizing light transfer technologies and renewable energy in vertical farming systems, Singapore can increase its capability in producing a higher yield of produce with a reduction in the power consumption. This would result in a more efficient use of electricity when growing produce, leading to an increase in sustainability and cost savings.